2016
DOI: 10.4103/1463-1741.178510
|View full text |Cite
|
Sign up to set email alerts
|

Student′s music exposure: Full-day personal dose measurements

Abstract: Previous studies have shown that collegiate level music students are exposed to potentially hazardous sound levels. Compared to professional musicians, collegiate level music students typically do not perform as frequently, but they are exposed to intense sounds during practice and rehearsal sessions. The purpose of the study was to determine the full-day exposure dose including individual practice and ensemble rehearsals for collegiate student musicians. Sixty-seven college students of classical music were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
0
15
1
Order By: Relevance
“…College marching band students’ auditory health is also at risk, as those students are regularly subjected to elevated noise levels (Chesky, 2008; Washnik, Phillips, & Teglas, 2016). Students are reluctant to wear hearing protection because of sound quality reductions (Jin, 2013).…”
Section: Challenges For Studentsmentioning
confidence: 99%
“…College marching band students’ auditory health is also at risk, as those students are regularly subjected to elevated noise levels (Chesky, 2008; Washnik, Phillips, & Teglas, 2016). Students are reluctant to wear hearing protection because of sound quality reductions (Jin, 2013).…”
Section: Challenges For Studentsmentioning
confidence: 99%
“…The present study may offer an alternative explanation for the observed association. Numerous studies have reported that musicians are exposed to loud traumatic sounds on a regular basis [ 60 – 62 ]. It is conceivable that musicians are likely to exhibit higher NEB than non-musicians which may subsequently influence the MOCR strength.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one billion teenagers and young adults (12–35 years) are at risk of noise-induced hearing loss due to hazardous recreational listening behaviors [ 1 ]. These behaviors include attendance at live music venues (nightclubs, festivals, concerts and bars), practising/producing music, DIY, engine noise and sports related noise [ 2 6 ]. In many instances, the risks of recreational noise exposure can be reduced through the use of hearing protection devices (earplugs and earmuffs).…”
Section: Introductionmentioning
confidence: 99%